Analisis Strategi Peningkatan Pajak Daerah di Kabupaten Deli Serdang Dalam Perspektif Ekonomi Islam - Batubara, Chuzaimah; Kamila, Kamila; Saragih, Al Manar (ITB AAS INDONESIA Surakarta, 2024)
This study aims to analyze the strategy of increasing local taxes in Deli Serdang Regency and how taxes are from an Islamic Economics perspective. This research is descriptive quantitative. The population in this study were all employees of the Regional Revenue Agency of Deli Serdang Regency. The sampling used was purposive sampling with the technique taken was saturated sampling. The analysis method used is Analytichal Hierarchy Process (AHP). The results of this study indicate that the global priority weight obtained the value of Human Resources Improvement of 0.537, the value of Improving the Supervision System of 0.208 and the value of Enforcement and Sanctioning of 0.254. The highest value / highest priority weight on the Alternative is Human Resources Improvement of 0.537, thus it can be concluded that the Priority Strategy for Increasing Regional Tax Revenue in Deli Serdang Regency is to increase human resources. Taxes in Islam are taken from the state to the people not based on their form but on the benefits and purpose of their implementation. According to Islam, there are three types of taxes, namely Jizyah (a tax imposed on non-Muslims in return for guarantees given by an Islamic state to them to protect their lives), Kharaj (a tax imposed on land obtained through force of arms), and Usyr ( trade taxes or customs duties).